2003
DOI: 10.1103/physrevb.67.115109
|View full text |Cite
|
Sign up to set email alerts
|

Korringa-Kohn-Rostoker nonlocal coherent-potential approximation

Abstract: We introduce the Korringa-Kohn-Rostocker nonlocal coherent-potential approximation ͑KKR-NLCPA͒ for describing the electronic structure of disordered systems. The KKR-NLCPA systematically provides a hierarchy of improvements upon the widely used KKR-CPA approach and includes nonlocal correlations in the disorder configurations by means of a self-consistently embedded cluster. The KKR-NLCPA method satisfies all of the requirements for a successful cluster generalization of the KKR-CPA; it remains fully causal, b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
116
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(118 citation statements)
references
References 30 publications
1
116
0
Order By: Relevance
“…This nonlocal CPA ͑NLCPA͒ theory is based on reciprocal space coarse-graining ideas introduced by Jarrell and Krishnamurthy, 42 originating from the dynamical cluster approximation ͑DCA͒. [43][44][45] The KKR-NLCPA 36,37 introduces an effective ͑translationally invariant͒ disorder term ␦G, which represents an effective propagator that accounts for all nonlocal scattering correlations on the electronic propagation due to disorder configurations and modifies the structure constants accordingly. By coarse-graining reciprocal space, one naturally introduces real space periodically repeating clusters.…”
Section: Introductionmentioning
confidence: 99%
“…This nonlocal CPA ͑NLCPA͒ theory is based on reciprocal space coarse-graining ideas introduced by Jarrell and Krishnamurthy, 42 originating from the dynamical cluster approximation ͑DCA͒. [43][44][45] The KKR-NLCPA 36,37 introduces an effective ͑translationally invariant͒ disorder term ␦G, which represents an effective propagator that accounts for all nonlocal scattering correlations on the electronic propagation due to disorder configurations and modifies the structure constants accordingly. By coarse-graining reciprocal space, one naturally introduces real space periodically repeating clusters.…”
Section: Introductionmentioning
confidence: 99%
“…2 in reciprocal space, to correctly describe a finite cluster still representative for the whole bulk. Jarrell et al, 20 and subsequently Rowlands et al, 21 have shown how this can be accomplished through a partitioning of the original Brillouin zone domain of integration respectful of the underlying lattice symmetries. This is now coarse-grained into N c tiles around a discrete set of cluster momenta K n , which remain defined only up to an arbitrary phase factor, further discussed below 24 .…”
Section: B the Non-local Cpa Solutionmentioning
confidence: 99%
“…20 To this date the technique has been developed only for simple lattices with just one element per unit cell, in the case of Strukturberichte A h , A2, A1 geometries. 21 Furthermore, this coarse-graining of the Brillouin zone leads to discontinuities in the k -dependent integrand of Eq.12, whenever tile boundaries are crossed. 24,26 We note here however a recent suggestion to overcome such limitation through an additional averaging step over various phase choices, to reobtain a smooth k -dependence 18 .…”
Section: B the Non-local Cpa Solutionmentioning
confidence: 99%
See 2 more Smart Citations